2008
DOI: 10.1016/j.cell.2008.05.031
|View full text |Cite
|
Sign up to set email alerts
|

An RNAi Screen of Chromatin Proteins Identifies Tip60-p400 as a Regulator of Embryonic Stem Cell Identity

Abstract: SUMMARY Proper regulation of chromatin structure is necessary for the maintenance of cell type-specific gene expression patterns. The embryonic stem cell (ESC) expression pattern governs self-renewal and pluripotency. Here, we present an RNAi screen in mouse ESCs of 1008 loci encoding chromatin proteins. We identified 68 proteins that exhibit diverse phenotypes upon knockdown (KD), including seven subunits of the Tip60-p400 complex. Phenotypic analyses revealed that Tip60-p400 is necessary to maintain characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

47
480
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(534 citation statements)
references
References 48 publications
47
480
0
Order By: Relevance
“…Thus, p400/mDomino appears to regulate both the p53-dependent and c-Myc-modulated expression of p21, which blocks cell proliferation and leads to cellular senescence. However, a recent study showed that the siRNA-mediated knockdown of p400/mDomino in mouse cells reduces the proliferation rate of embryonic stem cells without p21 up-regulation, and has only a modest effect on the cell cycle of embryonic fibroblasts (23). This discrepancy in the effect of p400 knockdown on cellular proliferation could be attributable to cell-type-specific roles of p400/mDomino, or different levels of residual p400/mDomino protein might have resulted in the distinct phenotypes in these knockdown experiments.…”
mentioning
confidence: 99%
“…Thus, p400/mDomino appears to regulate both the p53-dependent and c-Myc-modulated expression of p21, which blocks cell proliferation and leads to cellular senescence. However, a recent study showed that the siRNA-mediated knockdown of p400/mDomino in mouse cells reduces the proliferation rate of embryonic stem cells without p21 up-regulation, and has only a modest effect on the cell cycle of embryonic fibroblasts (23). This discrepancy in the effect of p400 knockdown on cellular proliferation could be attributable to cell-type-specific roles of p400/mDomino, or different levels of residual p400/mDomino protein might have resulted in the distinct phenotypes in these knockdown experiments.…”
mentioning
confidence: 99%
“…Tip60 depletion in Caenorhabditis elegans results in premature cell cycle exit and differentiation of one particular cell type, the vulval cells 45 . Second, Tip60 was shown to be essential for the maintenance of embryonic stem cell identity, probably through regulation of the cell cycle and proliferation and by repressing the expression of multiple differentiation genes 39 . Interestingly, Tip60 knockdown had only very modest effects on MEF cell cycle distribution and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Several genome-wide RNAi screens have identified factors required for self-renewal, and cohesin and condensin have shown up time and time again [13,[63][64][65][66]. Since self-renewal implies proliferation, these screens will identify a large fraction of genes required for DNA replication, repair and cell division.…”
Section: A Role For Cohesin In Gene Expression and Development: Disenmentioning
confidence: 99%